Is leadership position related to more social inclusion, happiness, and satisfaction with life? The importance of power distance index - Stelmokienė, Aurelija; Jarašiūnaitė-Fedosejeva, Gabija (Business: Theory and Practice, 2023)
A leadership position is associated with influence, success, and power, especially in cultures with high power distance (Zheng et al., 2018). Yet, we still know little about leaders’ wellbeing in different cultures. Therefore, the purpose of this paper is to investigate if a leadership position is related to more happiness, satisfaction with life and social inclusion.Additionally, it is presumed that this relationship could differ in countries with different power distance scores. European Social Survey (ESS) data from Round 9, edition 2.0 was employed to test research propositions. 23 079 currently working respondents’ data whose main activity was paid work (7130 of them having leadership positions) were analysed. The study results showed that leaders were more satisfied with life, happier, and more socially included than people who did not have a leadership position in their workplace. The power distance index acted as a moderator only in the model of happiness prediction. However, this country related variable had a significant direct negative effect on predicting peoples’ happiness and satisfaction with life, and direct positive effect on social inclusion. Regarding results, a shared leadership perspective could be proposed to have more satisfied with life, happy and socially active members in the organization.